(untitled) - Omernick, Mattheu (Indianapolis, Ind., 2004)
The key word here is art: the dynamic 3D art that defines the world of computer games. This book teaches you everything you need to know about the planning, modeling, texturing, lighting, effects creation, and interface design that go into creating today's most advanced and stunning video games. . You'll be learning from a master-veteran 3D artist and instructor Matthew Omernick-as you progress through the carefully chosen, software-agnostic tutorials that make up this beautiful, full-color volume. The end result will be skills you can apply to whatever 3D tool you choose and whatever wildly imaginative game you can think up. Through a unique combination of explanation, tutorials, and real world documentation-including discussions of the creative process entailed in some of today's most popular games augmented by screen captures and descriptions-you'll quickly come to understand the workflow, tools, and techniques required to be a successful game artist. In add! ition to learning the ropes of game art, you’ll also find in depth tutorials and techniques that apply to all aspects of 3D graphics. Whether you are using Photoshop, 3ds max, Maya, or any other computer graphics software, you’ll find a wealth of information that you can continue to come back to time and time again.
Keywords: Computer graphics,Computer animation,Three-dimensional display systems,Video games; Design